Conventional Harvest Index Methods may Overestimate Biomass and Nutrient Removal from Abscising Crop Species. Issue 22 (16th December 2018) - Jani, Arun D.; Mulvaney, Michael J.; Leon, Ramon G.; Rowland, Diane L.; Erickson, John E.; Wood, C. Wesley
ABSTRACT: Harvest index (HI) is conventionally measured using end-of-season biomass, but leaf abscission during crop growth can represent a substantial portion of total crop biomass for several species. A field study was conducted in Florida, USA, to determine the accuracy of conventional and alternative HI methods using sesame ( Sesamum indicum L.) as a model species and to assess biomass and nutrient contributions from abscised leaves. Seed and nutrient HI was determined from three cultivars using the following four methods: (1) total biomass method that included both end-of-season and seasonal abscised biomass; (2) conventional method based solely on end-of-season biomass; (3) early-bloom method in which biomass collected during early-bloom stage was used as the nonseed biomass component; (4) mid-bloom method where biomass from mid-bloom stage was used for nonseed biomass. Early- and mid-bloom methods overestimated all HI and underestimated biomass and nutrient return to the soil. Most nutrient HI based on the conventional method was higher than the values based on the total biomass method. Compared to the total biomass method, the conventional method underestimated biomass and nutrient return to soil per ha by 714.8 kg biomass, 28.5 kg nitrogen, 3.6 kg phosphorus, 34.7 potassium, 4.6 magnesium, 25.7 calcium, 3.4 kg sulfur, 26.5 g boron, 361 g zinc, 25.9 g manganese, 527.2 g iron, and 18.7 g copper. Including abscised leaves when determining HI may not be feasible in field experiments due to labor constraints but is an option when measuring HI for species under similar management at regional scales to improve estimates of nutrient cycling.